Analisis Perbandingan Kualitas Produk Dan Harga Antara Motor KLX Dan CRF di Kota Bima - M. Adhar; Kartin Aprianti (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
This research aims to determine whether there are differences in quality and price between KLX and CRF motorbikes in the city of Bima. The sample in this study was 50 KLX motorbike users and 50 CRF motorbike users. Data collection techniques use observation, questionnaires, literature study. The data analysis technique uses the paired sample t test. The research results show that there is no difference in product quality and price between KLX and CRF motorbikes in Bima City.